BUSINESS VALUE-ADDED WITHIN THE CIRCULAR BUSINESS MODEL: A MULTIPLE CASE ANALYSIS - Dede Iskandar Siregar; Intan Diane Binangkit (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The traditional business model (linear economy) dominating the current industry has caused many environmental problems and depletes natural resources. The Circular Business Model (CBM) is believed to be a potential solution to this problem. Apart from being more environmentally friendly, this approach is also more profitable in a business sense. This present study aims to analyze the business value-added from the CBM. This study was conducted using a qualitative case study approach in four SMEs located in Pekanbaru city. The data collection process was carried out nobly from March-July 2020 through observation, interview, and study document. Observation and interviews were carried out simultaneously with owners, managers, and employees. The final data collection was carried out by analyzing documents obtained directly from the company, website, and press releases. The results showed that business value-added obtained from implementing CBM includes cost reduction (raw materials, operational) and additional revenue from the sale of used materials and production waste. Keywords: circular economy, business model, value-added, sustainability